Między etnografią a archeologią doświadczalną, czyli o smaku świątecznych szynek - Andrzejewska, Aldona; Andrzejewski, Aleksander (Zeszyty Wiejskie, 2016)
One of the main problems of living human was food storage. The biggest problem was with perishable meat. So, in order to keep meat in good condition, people dried or smoked it. Smoking is a method of preserving food: meat, meat products, fish, cheese, malt, etc. by smoke. As a result of this process foods acquire a specific aroma, taste and color of the surface. The construction of the smokehouse was developed in the Middle Ages, and since then, in principle, it has not changed. The device consists of a smoking chamber, furnaces and runner smoke from the furnace to the smoking chamber. Sometimes, in the old homes, smokehouses were built directly into the chimney stove that heated the house. Then there was a description of the process of preparing homemade smoked hams. These activities included the preparation of a couple of hams. The first stage is salting. Then smoking takes place in a specially prepared smokehouse by means of smoke of plum and cherry wood.